2014
DOI: 10.5304/jafscd.2014.051.010
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Cost of a Balanced Diet, as a Function of Travel Time and Food Price

Abstract: We present a new method for analyzing spatial variation in the cost of a balanced diet, as an alternative to food desert classification. Our specific hypothesis is that the cost of a balanced diet varies according to where one lives, as a function of travel and food item costs. We collected price data for the USDA Thrifty Food Plan from approximately 30 percent of food retail outlets of various kinds in the three Gulf Coast counties of Mississippi, and these prices were extrapolated to the remaining stores. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…When examining such racial disparities, it is critical to consider the historical impact of policy in driving the disparities. Columbus ranks 78 out of the 318 most racially segregated cities in the U.S. [ 63 ]. The racial segregation of American cities is a cumulative result of policies enacted throughout the twentieth century.…”
Section: Discussionmentioning
confidence: 99%
“…When examining such racial disparities, it is critical to consider the historical impact of policy in driving the disparities. Columbus ranks 78 out of the 318 most racially segregated cities in the U.S. [ 63 ]. The racial segregation of American cities is a cumulative result of policies enacted throughout the twentieth century.…”
Section: Discussionmentioning
confidence: 99%
“…There is now a rather substantial body of literature on the role that time plays in nutrition-related outcomes, ranging from lower diet quality being associated with lower time in food preparation (e.g., Jabs and Devine 2006;Monsiavais, Aggarwal, and Drewnowski 2014), to mealtime planning and food insecurity (Fiese et al 2016) and healthy child weight (Fiese, Hammons, and Grigsby-Toussaint 2012). Marshall and Pires (2017) and Hilbert et al (2016) find that travel costs, which are directly proportional to time, are more important in determining grocery choices and diet quality than food prices. Landfield, Fraumeni, and Vojtech (2009) argue that a timeadjusted food price index helps better explain the increase in convenience food consumption than just the unadjusted price index.…”
Section: A Poverty Index Extension Of the Normalized Money Expenditurementioning
confidence: 99%
“…Low-income individuals have cited cost, time, transportation, habit, and food preferences as potential barriers to using DTC operations for food purchasing (Leone et al, 2012;McGuirt, Pitts, Seguin, Bentley, DeMarco, & Ammerman, 2018;McGuirt, Ward, Elliott, Bullock, & Pitts, 2014;Racine, Smith Vaughn, & Laditka, 2010). Hilbert, Evans-Cowley,Reece, Rogers, Ake, and Hoy (2014) found that rural lowincome populations may be particularly vulnerable to food-access issues because of transportation costs associated with pursuing a healthy diet, and that policy efforts should always consider placespecific factors given variation in costs.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%